Epimedii Herba: An ancient Chinese herbal medicine in the prevention and treatment of rheumatoid arthritis - Zhang, Liu-Bo; Yan, Yu; He, Jun; Wang, Pei-Pei; Chen, Xin; Lan, Tian-Yi; Guo, Yu-Xuan; Wang, Jin-Ping; Luo, Jing; Yan, Ze-Ran; Xu, Yuan; Tao, Qing-Wen (Frontiers in Chemistry, 2022)
Rheumatoid arthritis (RA) is a chronic, progressive inflammatory and systemic autoimmune disease resulting in severe joint destruction, lifelong suffering and considerable disability. Diverse prescriptions of traditional Chinese medicine (TCM) containing Epimedii Herba (EH) achieve greatly curative effects against RA. The present review aims to systemically summarize the therapeutic effect, pharmacological mechanism, bioavailability and safety assessment of EH to provide a novel insight for subsequent studies. The search terms included were “Epimedii Herba”, “yinyanghuo”, “arthritis, rheumatoid” and “Rheumatoid Arthritis”, and relevant literatures were collected on the database such as Google Scholar, Pubmed, Web of Science and CNKI. In this review, 15 compounds from EH for the treatment of RA were summarized from the aspects of anti-inflammatory, immunoregulatory, cartilage and bone protective, antiangiogenic and antioxidant activities. Although EH has been frequently used to treat RA in clinical practice, studies on mechanisms of these activities are still scarce. Various compounds of EH have the multifunctional traits in the treatment of RA, so EH may be a great complementary medicine option and it is necessary to pay more attention to further research and development.